2012
DOI: 10.1002/jbmr.1598
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronic acid improves bone mineral density in pediatric spinal cord injury

Abstract: Spinal cord injury (SCI) is associated with rapid and sustained bone loss and increase risk of fracture. Disuse is the primary cause for bone loss, although neural and hormonal changes may also contribute via different mechanisms. Bisphosphonates are used widely to treat osteoporosis in adults and are used increasingly for primary and secondary osteoporosis in children. Current data are insufficient to recommend routine use of bisphosphonates for fracture prevention in adult patients post-SCI and there are no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…The improvement of BMD with only one infusion of zoledronic acid every 6 months for 1 year, and 3 monthly infusion for 12 months, were similar in pediatric spinal cord injury [ 26 ]. Also, one single infusion of zoledronic acid in adult patients reduces >30% the rate of clinical fractures over 3 years of follow up, compared with placebo [ 27 ].…”
Section: Molecular Mechanisms Of Actions Of Bisphosphonatesmentioning
confidence: 99%
“…The improvement of BMD with only one infusion of zoledronic acid every 6 months for 1 year, and 3 monthly infusion for 12 months, were similar in pediatric spinal cord injury [ 26 ]. Also, one single infusion of zoledronic acid in adult patients reduces >30% the rate of clinical fractures over 3 years of follow up, compared with placebo [ 27 ].…”
Section: Molecular Mechanisms Of Actions Of Bisphosphonatesmentioning
confidence: 99%
“…The majority show a mild reduction in bone loss that is variably maintained, and results are insufficient to support routine use in patients without a history of fractures [84]. Data for bisphosphonate use in children with SCIs are limited to a single case report, in which a child treated with zoledronic acid for 18 months demonstrated significant gains in BMD [85]. Although use of bisphosphonates to prevent bone loss in adults with SCIs is not well supported, the potential for added benefits during bone modeling and skeletal growth justify additional investigation into the use of these medications in children.…”
Section: Low Bmd In Childrenmentioning
confidence: 99%
“…Ossification in the thoracic spine of one patient and in the rib of the other patient were observed (13). The BMD, as measured by DEXA, increases with the administration of ZA in post-menopausal osteoporosis patients (14), pediatric patients with spinal cord injury (15) and children with type III osteogenesis imperfecta (16). However, to the best of our knowledge, no study has revealed an improved BMD in the metastatic sites following the administration of ZA.…”
Section: Discussionmentioning
confidence: 99%